An electret film and a method for manufacturing the same

CN118257066BActive Publication Date: 2026-10-27刘钢
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410114654.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2026-10-27
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

但目前驻极贴的表面电荷密度较低,因此,亟需提供一种驻极体膜,提高表面电荷,及其电荷稳定性

Benefits of technology

[0025](1)与现有技术相比,本发明提供的驻极体膜高度极化,具有较高的表面电荷密度,表面电位可以达到8~10kV。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118257066B_ABST
    Figure CN118257066B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of materials, and particularly discloses an electret film and a preparation method thereof, which comprises a polyvinylidene fluoride molecular chain structure or a chain structure of a chlorotrifluoroethylene and ethylene alcohol copolymer, and the surface potential of the electret film is 8-10 kV. The electret film provided by the application is highly polarized, has a high surface charge density, and the surface potential can reach 8-10 kV. The electret film preparation method provided by the application shortens the film forming time, accelerates the preparation speed of the electret film, and the preparation process is carried out at room temperature, so that the energy consumption is small, and the surface potential of the prepared electret film is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, specifically to an electret film and its preparation method. Background Technology

[0002] Existing methods for producing electret patches include the method disclosed in patent CN110090316A, which uses a high-dielectric film and high-voltage corona discharge to charge the surface of the electret dressing. The surface charge from corona discharge cannot be permanently maintained and is easily affected by the environment. Polar molecular compounds are polarized using a high electric field, requiring temperature control during polarization to facilitate dipole orientation, and rapid cooling after polarization to fix the dipoles. Patent CN105788863A discloses a process for manufacturing polyvinylidene fluoride electrets, which involves corona polarization of a polyvinylidene fluoride film at high temperatures (70℃~200℃) for 5~10 minutes, limiting the yield of electret patches and resulting in higher costs.

[0003] The electret effect of electret patches interacts with the body to enhance immunity. Electret patches are increasingly used in the medical field for purposes such as promoting blood circulation and relieving pain, treating bone injuries, and administering medication through the skin. However, current electret patches have a low surface charge density; therefore, there is an urgent need to provide an electret film to improve surface charge and its stability. Summary of the Invention

[0004] To address the aforementioned problems, the first objective of this invention is to provide an electret film that is highly polarized, has a high surface charge density, and a surface potential that can reach 8–10 kV.

[0005] The second objective of this invention is to provide a method for preparing electret films. This method shortens the film formation time, accelerates the preparation speed of electret films, and the preparation process is carried out at room temperature with low energy consumption. Furthermore, the surface potential of the prepared electret film is stable.

[0006] The first technical solution adopted in this invention is: an electret membrane comprising a polyvinylidene fluoride molecular chain structure or a chain structure of trifluorochloroethylene and vinyl acetate, wherein the surface potential of the electret membrane is 8-10kV.

[0007] Preferably, the polyvinylidene fluoride molecular chain structure is β-type, and the structure is as follows:

[0008]

[0009] Preferably, the chain structure of the trifluorochloroethylene and vinyl acetate is as follows:

[0010]

[0011] The second technical solution of the present invention is a method for preparing an electret film, comprising:

[0012] Step 1: Prepare the polyvinylidene fluoride electrospinning solution;

[0013] Step 2: Prepare an electret membrane from the polyvinylidene fluoride electrospinning solution using electrospinning.

[0014] Preferably, the polyvinylidene fluoride mass concentration in the polyvinylidene fluoride electrospinning solution is 10-12%.

[0015] Preferably, 0.5-5% by mass of a polarizing agent is added to the polyvinylidene fluoride electrospinning solution;

[0016] The polarizing agent is nano zinc oxide.

[0017] Preferably, the process parameters of the electrospinning method include: temperature 40-50℃, relative humidity 20-30%, distance between the electrospinning nozzle and the receiving device 18cm, negative voltage of 28-35kV connected to the nozzle, adjusting the electric field strength to prevent the formation of bead-like particles during spinning, and spinning speed of 1ml / h per nozzle.

[0018] Preferred, including:

[0019] Step 1: Alcohololysis of the copolymer of trifluorochloroethylene and vinyl acetate to obtain the copolymer of trifluorochloroethylene and vinyl alcohol;

[0020] Step 2: Prepare the electrospinning solution of the copolymer of trifluorochloroethylene and vinyl alcohol;

[0021] Step 3: Prepare an electret membrane from the electrospinning solution using electrospinning.

[0022] Preferably, the electrospinning solution for the trifluorochloroethylene and ethylene alcohol copolymer is prepared by dissolving the trifluorochloroethylene and ethylene alcohol copolymer in dimethylformamide to obtain the electrospinning solution for the trifluorochloroethylene and ethylene alcohol copolymer; the mass fraction of the trifluorochloroethylene and ethylene alcohol copolymer is 10-20%.

[0023] Preferably, the process parameters of the electrospinning method include: temperature 30-40℃, distance between the electrospinning nozzle and the receiving device 18cm, and single nozzle spinning rate 5ml / h.

[0024] The beneficial effects of the above technical solution are as follows:

[0025] (1) Compared with the prior art, the electret film provided by the present invention is highly polarized, has a high surface charge density, and the surface potential can reach 8 to 10 kV.

[0026] (2) The electret membrane provided by this invention has good effects in practical applications. The interaction between the electret effect and the organism can enhance immunity. It meets the requirements for promoting blood circulation and relieving pain, treating bone injuries, and administering drugs through the skin.

[0027] (3) The electret film preparation method provided by the present invention shortens the film formation time, accelerates the preparation speed of electret film, and the preparation process is carried out at room temperature with low energy consumption, and the surface potential of the prepared electret film is stable. Attached Figure Description

[0028] Figure 1 A molecular chain structure diagram of α-type polyvinylidene fluoride provided in one embodiment of the present invention;

[0029] Figure 2 A molecular chain structure diagram of β-type polyvinylidene fluoride provided in one embodiment of the present invention;

[0030] Figure 3 The diagram shows the chain structure of trifluorochloroethylene and vinyl acetate provided in Embodiment 5 of the present invention. Detailed Implementation

[0031] The embodiments of this application will be described in further detail below. Obviously, the described embodiments are only a part of the embodiments of this application, and not an exhaustive list of all embodiments. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.

[0032] The terms “first,” “second,” etc. (if applicable) in the specification and claims are used to distinguish similar objects and are not necessarily used to describe a particular order or sequence. It should be understood that such data used in this way can be interchanged where appropriate so that the embodiments described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms “comprising” and “having,” and any variations thereof, are intended to cover a non-exclusive inclusion, such as a process, method, system, product, or apparatus that comprises a series of steps or units, not necessarily limited to those explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0033] It should be understood that the term "and / or" used in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this article generally indicates that the preceding and following related objects have an "or" relationship.

[0034] Example 1

[0035] Add 0.5% nano-zinc oxide, a polarizing agent, to the electrospinning solution of polyvinylidene fluoride (PVDF) to prepare a uniformly dispersed electrospinning solution. Preferably, the PVDF concentration in the electrospinning solution is 10%, and electrospinning is performed at a temperature of 40–50°C and a relative humidity of 20–30%. The distance between the electrospinning nozzle and the receiving device is 18 cm, and the nozzle is connected to a negative 30 kV voltage. Adjust the electric field strength to prevent the formation of bead-like particles during spinning. The spinning speed per nozzle is 1 ml / h to ensure the α-type molecular chain structure of PVDF (e.g., ...) Figure 1 ) more polarized into β type (e.g. Figure 2 The β-type is an identical structure with a large dipole moment that provides surface charge to the electret film. In this embodiment, the electret film has a surface potential of 8 kV, and the mass fraction of the β phase in the crystal is 75%.

[0036] Example 2

[0037] A uniformly dispersed electrospinning solution is prepared by adding 1.5% nano-zinc oxide as a polarizing agent to the polyvinylidene fluoride (PVDF) electrospinning solution. Preferably, the PVDF concentration in the electrospinning solution is 10%, and electrospinning is carried out at a temperature of 40–50°C and a relative humidity of 20–30%. The distance between the electrospinning nozzle and the receiving device is 18 cm, and the nozzle is connected to a negative 30 kV. The electric field strength is adjusted to prevent the formation of bead-like particles during spinning. The spinning speed per nozzle is 1 ml / h to ensure that the α-type PVDF molecular chain structure is more polarized into the β-type. The β-type has a large dipole moment, providing surface charge to the electret film. In this embodiment, the electret film has a surface potential of 8.5 kV, and the mass fraction of the β-phase in the crystal is 80%.

[0038] Example 3

[0039] A uniformly dispersed electrospinning solution is prepared by adding 5% nano-zinc oxide as a polarizing agent to the polyvinylidene fluoride (PVDF) electrospinning solution. Preferably, the PVDF concentration in the electrospinning solution is 12%, and electrospinning is performed at a temperature of 40–50°C and a relative humidity of 20–30%. The distance between the electrospinning nozzle and the receiving device is 18 cm, and the nozzle is connected to a negative 30 kV voltage. The electric field strength is adjusted to prevent the formation of bead-like particles during spinning. The spinning speed per nozzle is 1 ml / h to ensure that the α-type PVDF molecular chain structure is more polarized into the β-type. The β-type has a large dipole moment, providing surface charge to the electret film. In this embodiment, the electret film has a surface potential of 10 kV, and the mass fraction of the β-phase in the crystal is 90%.

[0040] Example 4

[0041] A uniformly dispersed electrospinning solution was prepared by adding 3% nano-zinc oxide as a polarizing agent to the polyvinylidene fluoride (PVDF) electrospinning solution. Preferably, the PVDF concentration in the electrospinning solution was 11%, and electrospinning was performed at a temperature of 40–50°C and a relative humidity of 20–30%. The distance between the electrospinning nozzle and the receiving device was 18 cm, and the nozzle was connected to a negative 30 kV voltage. The electric field strength was adjusted to prevent the formation of bead-like particles during spinning. The spinning speed per nozzle was 1 ml / h to ensure that the α-type PVDF molecular chain structure was more polarized into the β-type. The β-type has a large dipole moment, providing surface charge to the electret film. In this embodiment, the electret film has a surface potential of 9 kV, and the mass fraction of the β-phase in the crystal is 85%.

[0042] Comparative Example 1

[0043] A uniformly dispersed electrospinning solution is prepared by electrospinning polyvinylidene fluoride (PVDF) without the addition of nano-zinc oxide as a polarizing agent. Preferably, the PVDF concentration in the electrospinning solution is 11%, and electrospinning is performed at a temperature of 40–50°C and a relative humidity of 20–30%. The distance between the electrospinning nozzle and the receiving device is 18 cm, and the nozzle is connected to a negative 30 kV voltage. The electric field strength is adjusted to prevent the formation of bead-like particles during spinning. The spinning speed per nozzle is 1 ml / h to ensure that the α-type PVDF molecular chain structure is more polarized into the β-type. The β-type has a large dipole moment, providing surface charge to the electret film. In this embodiment, the electret film has a surface potential of 6 kV, and the mass fraction of the β-phase in the crystal is 60%.

[0044] Example 5

[0045] Electret therapeutic membranes were prepared based on a copolymer of trifluorochloroethylene and vinyl acetate. A characteristic of the trifluorochloroethylene and vinyl acetate copolymer is that it yields essentially alternating copolymer molecules. Alcohololysis of the copolymer yields a copolymer of trifluorochloroethylene and vinyl alcohol. Chain structure analysis shows that the trifluorochloroethylene and vinyl alcohol segments can be considered as a whole; the trifluorochloroethylene segment is a very strong electron-withdrawing group, thus forming a very strong dipole. A 20% solution of the trifluorochloroethylene and vinyl alcohol copolymer was prepared by electrospinning without the addition of a polarizing agent. The spinning temperature was controlled at 30–40°C, the distance between the electrospinning nozzle and the receiving device was 18 cm, the nozzle was connected to -28 kV, and the single nozzle spin rate was 5 ml / h. The chain structure of trifluorochloroethylene and vinyl acetate is shown below. Figure 3 As shown. In this embodiment, the electret film has a surface potential of up to 10kV.

[0046] Example 6

[0047] Electret therapeutic membranes were prepared based on a copolymer of trifluorochloroethylene and vinyl acetate. A characteristic of the trifluorochloroethylene and vinyl acetate copolymer is that it yields essentially alternating copolymer molecules. Alcohololysis of the copolymer yields a copolymer of trifluorochloroethylene and vinyl alcohol. Chain structure analysis shows that the trifluorochloroethylene and vinyl alcohol segments, considered as a whole, constitute a strong dipole because the trifluorochloroethylene segments are strong electron-withdrawing groups. A 10% solution of the trifluorochloroethylene and vinyl alcohol copolymer was dissolved in dimethylformamide and electrospun without the addition of a polarizing agent. The spinning temperature was controlled at 30–40°C, the distance between the electrospinning nozzle and the receiving device was 18 cm, the nozzle was connected to -28 kV, and the single nozzle spinning rate was 5 ml / h. The electret membrane of this embodiment achieved a surface potential of 10 kV.

[0048] Comparative Example 2

[0049] The mass fractions of β phase content in polyvinylidene fluoride electrospun films (PVDF) obtained through different treatments in the prior art are shown in Table 1 below.

[0050] Table 1. Crystallinity of PVDF obtained after different treatments and mass fraction of β phase in the crystals.

[0051] PVDF powder 47.1 0 PVDF solution casting film 30.0 0.5 PVDF solution-cast film (polarized) 30.7 56.8 Electrospun PVDF fiber membrane 31.0 54.8

[0052] As can be seen from the table, the β phase content of the membrane obtained by electrospinning is only 54.8%, and the surface potential of the membrane is not high compared with the electret membrane provided by this invention.

[0053] Evaluation of the application effect of electret membrane:

[0054] The 10-20 microamp microcurrent generated by the electret membrane increases the transmembrane transport of K and Ca ions, thereby activating the intracellular cyclic adenosine monophosphate system. This can accelerate the transformation of osteoblasts into osteocytes and promote protein and collagen fiber synthesis. The negative electric field effect can weaken the positive electric field effect of damaged tissue, gradually eliminate the damage potential difference, increase cell activity, and effectively relieve pain.

[0055] Feedback from users in the surrounding area included: reduced pain from fatigue, sprains, strains, and contusions; faster healing; and significant reduction in bruising. When applied to gout areas, the condition quickly and noticeably improved.

[0056] When applied to the navel, it is effective in treating constipation and diarrhea; when applied to the stomach, it can relieve bloating and reduce stomach pain; when applied to the cervical spine, it is highly effective in relieving neck discomfort and accelerating blood circulation.

[0057] It is evident that the electret film and its preparation method provided by this invention have significant advantages over existing technologies, improving the surface potential of the electret film and achieving a stable high surface potential. Specifically, a copolymer of trifluorochloroethylene and vinyl acetate is alcoholyzed to form a copolymer of trifluorochloroethylene and vinyl alcohol. This copolymer has a stronger dipole moment than polyvinylidene fluoride (PVDF), resulting in an electrospinning speed five times faster than PVDF. The basic principle of electrospinning is that under a high electric field, the spinning solution polarizes the molecules to form fibers, which then reach the receiving device under the influence of the electric current; the greater the force, the faster the spinning solution propels the fiber. The surface tension of the electrospinning solution of the trifluorochloroethylene and vinyl alcohol copolymer is comparable to that of PVDF, and electrospinning is performed at room temperature, resulting in a faster propulsion speed of the spinning solution.

[0058] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing an electret film, characterized in that, The electret film has a chain structure of a copolymer of trifluorochloroethylene and vinyl alcohol, and its surface potential is 8~10kV; the preparation method includes: Step 1: Alcohololysis of the copolymer of trifluorochloroethylene and vinyl acetate to obtain the copolymer of trifluorochloroethylene and vinyl alcohol; Step 2: Prepare the electrospinning solution of the copolymer of trifluorochloroethylene and vinyl alcohol; Step 3: Prepare an electret film from the electrospinning solution using electrospinning. Step two includes: dissolving trifluorochloroethylene and vinyl alcohol copolymer in dimethylformamide to obtain an electrospinning solution of trifluorochloroethylene and vinyl alcohol copolymer; the mass fraction of trifluorochloroethylene and vinyl alcohol copolymer in the electrospinning solution is 10~20%.

2. The method for preparing the electret film according to claim 1, characterized in that, The process parameters of the electrospinning method include: temperature 30~40℃, distance between the electrospinning nozzle and the receiving device 18cm, and single nozzle spinning rate 5ml / h.

Citation Information

Patent Citations

  • Preparation method for polyvinylidene fluoride thin film electret

    CN105788863A

  • Anti-adhesion electret dressing and preparation method thereof

    CN110090316A

  • Composite nanofiber membrane as well as preparation method and application thereof

    CN115976740A

  • Method for producing fluororesin fiber, filter medium for air filter and method for producing the same

    JP2013139661A